2012
DOI: 10.1002/ajp.22107
|View full text |Cite
|
Sign up to set email alerts
|

Latent Variables Affecting Behavioral Response to the Human Intruder Test in Infant Rhesus Macaques (Macaca mulatta)

Abstract: The human intruder test is a testing paradigm designed to measure rhesus macaques’ behavioral responses to a stressful and threatening situation. In the test, an unfamiliar human positions him/herself in various threatening positions relative to a caged macaque. This paradigm has been utilized for over twenty years to measure a variety of behavioral constructs, including fear and anxiety, behavioral inhibition, emotionality, and aggression. To date there have been no attempts to evaluate comprehensively the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 43 publications
2
60
0
Order By: Relevance
“…Importantly, the structural and functional brain changes we observed corresponded with changes in emotional behavior. While studies have demonstrated an impact of nursery-rearing on brain development and behavior (68, 69), rearing conditions and handling experiences were the same for control and ZIKV-infected RM infants in this study. ZIKV-infected infants were not impaired in their ability to produce emotional responses, but instead exhibited an atypical emotional response based on the salience of the threat presented.…”
Section: Discussionmentioning
confidence: 75%
“…Importantly, the structural and functional brain changes we observed corresponded with changes in emotional behavior. While studies have demonstrated an impact of nursery-rearing on brain development and behavior (68, 69), rearing conditions and handling experiences were the same for control and ZIKV-infected RM infants in this study. ZIKV-infected infants were not impaired in their ability to produce emotional responses, but instead exhibited an atypical emotional response based on the salience of the threat presented.…”
Section: Discussionmentioning
confidence: 75%
“…The approach of a human stranger is an established laboratory stimulus to elicit defensive behavior in rhesus macaques (Willette et al, 2007; Rogers et al, 2008; Gottlieb and Capitanio, 2013). If male rhesus perceives a human observer as threatening, depressive-like responding might be suppressed in lieu of a defensive response.…”
Section: Discussionmentioning
confidence: 99%
“…We recorded the behaviors described above, plus position information. Exploratory and confirmatory factor analyses revealed a four‐factor structure to the data (Gottlieb & Capitanio, ) labeled activity (active, cage‐shake, environment explore), emotionality (convulsive jerk, fear grimace, self‐clasp, coo vocalization), aggression (threat, bark vocalization, other vocalization), and displacement (i.e., anxiety) (tooth grind, yawn). Factor scores for each animal were z‐scored within assessment year.…”
Section: Methodsmentioning
confidence: 99%